Training in Digital Skills in Early Childhood Education Teachers: The Case of the University of La Laguna - Pérez-Jorge, David; Rodríguez-Jiménez, María del Carmen; Gutiérrez-Barroso, Josué; Castro-León, Fátima (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Information and Communication Technologies (ICT) have become essential tools for the development of quality educational practices. The special situation of COVID-19 has evidenced the problem of the teacher training. This work investigates the perception of the future teachers of Early Childhood Education about the use of ICT and the policies developed by the Government of the Canary Islands regarding the provision of resources, materials and training. The study had a sample of 110 teachers in training from the University of La Laguna, the results showed agreement regarding the quality and quantity of training received, however, despite not showing interest in continuous training in ICT, they consider fundamentally mastering this competence to improve the quality of the educational response in the Canary Islands.